Substrate Specificity of the Nonribosomal Peptide Synthetase PvdD from Pseudomonas aeruginosa - Ackerley, David F. (American Society for Microbiology, 2003)
Pseudomonas aeruginosa PAO1 secretes a siderophore, pyoverdine(PAO), which contains a short peptide attached to a dihydroxyquinoline moiety. Synthesis of this peptide is thought to be catalyzed by nonribosomal peptide synthetases, one of which is encoded by the pvdD gene. The first module of pvdD was overexpressed in Escherichia coli, and the protein product was purified. l-Threonine, one of the amino acid residues in pyoverdine(PAO), was an effective substrate for the recombinant protein in ATP-PP(i) exchange assays, showing that PvdD has peptide synthetase activity. Other amino acids, including d-threonine, l-serine, and l-allo-threonine, were not effective substrates, indicating that PvdD has a high degree of substrate specificity. A three-dimensional modeling approach enabled us to identify amino acids that are likely to be critical in determining the substrate specificity of PvdD and to explore the likely basis of the high substrate selectivity. The approach described here may be useful for analysis of other peptide synthetases.